Expression profile of microRNAs related with viral infectivity, inflammatory response, and immune activation in people living with HIV - Cuesta-Sancho, Sara; Márquez-Ruiz, Denisse; Illanes-Álvarez, Francisco; Campaña-Gómez, Irene; Martín-Aspas, Andrés; Trujillo-Soto, María Teresa; Romero, Alberto; Galán, Fátima; Rodríguez-Iglesias, Manuel; Márquez-Coello, Mercedes; Girón-González, José-Antonio (Frontiers in Microbiology, 2023)
Objective To evaluate the serum expression of microRNAs (miRNAs) with ability to modulate the human immunodeficiency (HIV) replication or inflammatory status in people living with HIV (PLWH). Methods Forty healthy controls and two groups of PLWH were evaluated: (a) Group 1 (n = 30), patients with detectable viral load at inclusion, analyzed before receiving antiretroviral therapy (ART) and 12 months after initiating it; (b) Group 2 (n = 55), PLWH with prolonged undetectable viral load. Intestinal barrier disruption (I-FABP) and bacterial translocation (16S rDNA) markers, inflammatory markers such as interleukin (IL)-6 and sCD163, immune activation and expression of specific miRNAs were evaluated. Results Serum concentrations of I-FABP, 16S rDNA, IL-6, sCD163 and activated T lymphocytes were increased in PLWH. Serum miR-34a was overexpressed at inclusion and remained elevated after ART. The expression of the remaining miRNAs that modulate HIV infectivity (miR-7, mir-29a, miR-150, and miR-223) was similar in PLWH and controls. Related to miRNAs implicated in inflammation (miR-21, miR-155, and miR-210), significant overexpression were observed in miR-21 and miR-210 levels in untreated PLWH, but levels were restored in those patients treated for a long period. Conclusion A sustained overexpression of miR-34a was detected even after prolonged HIV controlled replication. miR-21 and miR-210 can be considered new markers of inflammation with high sensitivity to its modifications.